Addressing directionality: Orientation failure and the systems of innovation heuristic. Towards reflexive governance - Ralf Lindner; Stephanie Daimer; Bernd Beckert; Nils Heyen; Jonathan Koehler; Benjamin Teufel; Philine Warnke; Sven Wydra (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
[Introduction] Since about 15 years, science, technology and innovation (STI) policies are increasingly geared towards addressing objectives reaching beyond an immediate economic focus on growth and competitiveness. This "normative turn" (Daimer et al. 2012) is expressed in the strategic reorientation of national and supranational STI policies to address the so-called `grand challenges' (Kallerud et al. 2013). Well known examples for this ongoing paradigm shift are the European Union's Europe 2020 strategy, the US Strategy for American Innovation or Germany's Hightech Strategy. What is more, the quest to address `grand challenges' such as health, demographic change, wellbeing and sustainability by the means of research and innovation is complemented by and propelled forward by the emerging discourse on responsible (research and) innovation. In essence, RRI aims at improving the alignment of the impacts of technology and innovation with societal demands and values as far as possible. The concept is inherently characterised by a high degree of normativity in order to provide necessary guidance as to what constitutes desired or `responsible' research and innovation (Randles et al. 2014; Lindner and Kuhlmann 2016). The prominent position of RRI in the European Union's research and innovation programme 'Horizon 2020' and the endorsement of the "Rome Declaration on RRI in Europe" by the European Council in 2014 indicate that RRI is increasingly developing relevance for policy, research funding and scientific communities. [...]
urn:nbn:de:0011-n-4087463
Keywords: 330